Проблемы тенденций развития Украины в современных условиях ведения бизнеса - Чмелева, Ольга Сергеевна; Виленская, К. М. (НТУ "ХПИ", 2015)
В статье представлено обоснование понятия «современные условия ведения бизнеса», раскрыты тенденции развития Украины в современных условиях ведения бизнеса на основе анализа данных рейтинга «Ведение бизнеса» (DoingBusiness) и индекса инвестиционной привлекательности (ЕВА index), определены основные проблемы тенденций развития Украины в современных условиях ведения бизнеса и основные направления их решения.

The article presents the rationale for the concept of "modern business climate", revealed positive and negative tendencies of development of Ukraine in today`s business climate based on the analysis of data ranking "Doing business" (Doing Business) and an index of investment attractiveness (EVA index), the main problems of Ukraine`s development trend in today`s business climate and the basic directions of their solution, the direction for the development chosen by the program "Ukraine 2020".
Problems of tendencies of development of Ukraine in modern conditions of doing business
Keywords: рейтинга "Ведение бизнеса"; инвестиционная привлекательность; международный индекс; modern business conditions; Doing Business; EVA index; EBA